(untitled) (Castilla. Estudios de Literatura, 2024)
Drawing from sources such as Cela’s correspondence, the censorship file, the manuscript, and the press of the time, this study identifies the diverse roots that informed the conception and construction of Pabellón de reposo. It attends to Cela’s personal experience with illness, the social impact of pulmonary conditions during that period, and the writer’s intention to fictionally elaborate on a pathographic narrative while acknowledging pre-existing ones. Furthermore, this research closely examines the novel’s manuscript in connection with its serialized publication in the pages of El Español, and its initial books releases (including translations), and it also explores its critical reception.